Professional literacy that Taiwan’s bag manufacturing industry talents should possess: Analyzing from a practical perspective - Fan, Jing-Yun (Frontiers in Psychology, 2023)
This research aimed to explore the professional literacies that should be possessed by Taiwan’s bag manufacturing industry talents. A qualitative research design was adopted. The outline of the interview on the professional literacy of Taiwan’s bag manufacturing industry talents was compiled, and seven interviewees were selected by purposive sampling from those who had worked (including supervisors) in Taiwan’s bag manufacturing industry for 21 to 42 years. One-on-one in-depth interviews with semi-structured interview questions were conducted. Using grounded theory, the content of the in-depth interviews was analyzed and discussed. This study summarized the professional literacy of bag manufacturing industry talents into three major aspects: knowledge, skills, and attitudes and values. Based on this, suggestions are made as a reference for the implementation of curriculum development for talent cultivation in higher education institutions, and a reference for the learning and on-the-job training of bag manufacturing industry practitioners in the workplace.